Genetic and biological properties of H10Nx influenza viruses in China - Yina Xu; Hailing Li; Haoyu Leng; Chaofan Su; Siqi Tang; Yongtao Wang; Shiwei Zhang; Yali Feng; Yanan Wu; Daxin Wang; Ying Zhang (Journal of Integrative Agriculture, 2024)
H10 subtype avian influenza viruses (AIV) have been circulating in China for 40 years. H10 AIVs in China have expanded their host range from wild birds to domestic poultry and mammals, even human. Most of the H10 subtype AIVs reported in China were isolate from the southeast part. We isolated an H10N3 AIV, A/Chicken/Liaoning/SY1080/2021 (SY1080), from live poultry market (LPM) in Liaoning Province of the Northeast China. SY1080 replicated efficiently in mice lungs and nasal turbinates without prior adaptation. We systematically compared SY1080 with other H10 subtype isolates in China. Phylogenetic analysis showed that SY1080 and most of the H10 strains belonged to the Eurasian lineage. H10 AIVs in China have formed 63 genotypes. SY1080 as well as the H10N3 strains from human infections belonged to G60 genotype. H10Nx AIV acquired multiple mammalian adaptive and virulence related mutations during circulation and the recent reassortants derived internal genes from chicken H9N2 AIVs. The H10Nx subtypes AIVs posed potential threat to public health. These results suggested we should strengthen the surveillance and evaluation of H10 subtype strains.